Classical Fiqh, State Authority, and Digital Governance: Islamic Legal Discourse on Cyber Law in Malaysia (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2026)
The rapid advancement of digital technology has generated legal challenges that are not explicitly addressed within classical Islamic jurisprudential texts. These challenges have become increasingly complex, as the regulatory frameworks governing social practices in the nation-state era are no longer exclusively grounded on the religious legal norms upheld by the Muslim community. This study aims to analyze Malaysian cyber laws pertaining to various cyber-related issues, including cryptocurrency, personal data protection, and cyberbullying. By integrating the concept of al-maskūt ‘anhu—a recognized space of legal silence in Islamic legal theory that permits contextual reasoning—with the notion of Islamic law as a discursive tradition, this study proposes a novel analytical framework for comprehending how modern state law can embody Islamic normative reasoning without reliance on explicit textual precedents. Empirically, it provides one of the first systematic analyses of Malaysian cyber law through this combined perspective, thereby repositioning the role of the state not as a competitor to Islamic legal authority but as a central agent in sustaining the continuity of Islamic legal discourse in the digital era. This study contributes to the field by demonstrating that contemporary cyber regulations in Malaysia should not be regarded merely as external or supplementary to Islamic law, but rather as integral components of an ongoing Islamic legal discourse shaped by state authority and bureaucratic governance.